2017
DOI: 10.1186/s40900-017-0064-0
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding Plain English summaries. A comparison of two approaches to improve the quality of Plain English summaries in research reports

Abstract: Plain English summaryThere is a need for the authors of research reports to be able to communicate their work clearly and effectively to readers who are not familiar with the research area. The National Institute for Health Research (NIHR), along with a number of other funding bodies and journals, require researchers to write short lay summaries, often termed plain English summaries (PESs), to make research accessible to the general public. Because many researchers write using technical, specialised language, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…The principle of engaging the public as consumers of research is still in its infancy. There is a good argument that the public should be informed about the findings of research studies, particularly those that are publicly funded, and previous evidence has confirmed that an appetite for this exists. However, it is clear that more work needs to be done in collaboration with the public to understand whether, and how, research should be disseminated beyond traditional scientific communities.…”
Section: Discussionmentioning
confidence: 99%
“…The principle of engaging the public as consumers of research is still in its infancy. There is a good argument that the public should be informed about the findings of research studies, particularly those that are publicly funded, and previous evidence has confirmed that an appetite for this exists. However, it is clear that more work needs to be done in collaboration with the public to understand whether, and how, research should be disseminated beyond traditional scientific communities.…”
Section: Discussionmentioning
confidence: 99%
“…Using a standard, instantly recognizable icon, such as that inFigure 2, to signpost PLS within an article would also help readers locate them easily. PLS should be developed as part of the full scientific article, by the authors (with professional writing support to ensure appropriate readability)3 and with patients/lay people where possible, and berequired at journal article submission so PLS can be peer-reviewed alongside all other elements of the article. They should be published outside any article paywall and be positioned or signposted to have equal prominence with other key parts of the article.…”
mentioning
confidence: 99%
“…Likewise, several studies by Lawson (2015), Kirkpatrick & Gaisford (2017), Rubab, (2018), (2019) were executed to transform the complex legal texts into simplified versions. These linguists found the visible difference among the audiences with reference to the intelligibility and time saving.…”
Section: Relevant Scholarshipmentioning
confidence: 99%